The differential impact of interactions outside the organization on employee well‐being. Issue 1 (2nd August 2018) - Bhave, Devasheesh P.; Halldórsson, Freyr; Kim, Eugene; Lefter, Alexandru M.
Abstract : We examine two different perspectives of interactions outside the organization: the relational work design perspective and the emotional labour perspective. The relational work design perspective suggests that interactions outside the organization have favourable outcomes for employees, whereas the emotional labour perspective suggests that such interactions have adverse outcomes for employees. Our goal is to reconcile findings from these two research streams. In Study 1, using data from employees working in diverse occupations, we find that interactions outside the organization have a positive indirect effect on employee well‐being via task significance, and a negative indirect effect on employee well‐being via surface acting. In Study 2, using data collected across two time points, we replicate these findings. In Study 3, we further extend these results and illustrate that interactional autonomy and interactional complexity are influential moderators that shape the strength of the mediated relationships. Our results aid in reconciling and extending findings from two different research streams, and enhance our understanding of the role of interactions outside the organization. Practitioner points: Managers should consider that employees' interactions outside the organization have the potential to improve their well‐being. Organizations could redesign jobs to enable employees in customer‐facing roles to have greater discretion in how they interact with their customers and also increase the variety of these interactions.